An in vitro study of the ability of three new continuous rotary heat-treated nickel-titanium files to shape curved root canals - Jimin Zhang; Wenyao Li; Zhiqing Yang; Li Wanga (Annali di Stomatologia)
Objectives: To compare the shaping ability of three new continuous rotary heat-treated nickel-titanium files in curved root canal. Methods: Sixty standard resin simulated root canals were randomly divided into three groups (n = 20): i-FILE X, Orodeka PLEX2.0, NIC GF File were used to instrument root canals. The instrumentation time was meticulously recorded. The root canals before and after instrumentation were injected with black and red ink respectively and images of the canals before and after instrumentation were captured using a digital camera. The images were imported into Photoshop 2019 software, overlaid, and the amount of root canal resin removed was measured using ImageJ 1.54f. The centering ability was recorded. Post-instrumentation root canal curvature was also measured by the Schneider method and with ImageJ 1.54f. The differences between the three groups were statistically analyzed in terms of 3 aspects: instrumentation time, centering ability and curvature. Results: The i-FILE X group had the shortest instrumentation time, followed by the GF File group, and the Orodeka group had the longest instrumentation time (P < 0.05). The i-FILE X group had better centering ability at 1 mm, 2 mm, 3 mm, 4 mm, and 9 mm from the simulated root canal observation point than the other two groups, and there was no statistically significant difference among the three groups at the 5 mm to 8 mm (P>0.05). The working curvature of the simulated root canals was reduced in all three groups and there was no statistical significance in the intergroup comparison of the curvatures of the three groups (P>0.05). Conclusions: The three continuous rotary heat-treated nickel-titanium files exhibited commendable preparatory molding capabilities and were able to adequately preserve the original curvature of the root canals. The i-FILE has been demonstrated to exhibit a reduced instrumentation time and enhanced centering ability within the apical curved area.